Biomimetic porous scaffolds containing decellularized small intestinal submucosa and Sr2+/Fe3+ co-doped hydroxyapatite accelerate angiogenesis/osteogenesis for bone regeneration. (2nd February 2022) - Cui, Wei; Yang, Liang; Ullah, Ismat; Yu, Keda; Zhao, Zhigang; Gao, Xinfeng; Liu, Tao; Liu, Ming; Li, Peng; Wang, Junwen; Guo, Xiaodong
Abstract: The design of bone scaffolds is predominately aimed to well reproduce the natural bony environment by imitating the architecture/composition of host bone. Such biomimetic biomaterials are gaining increasing attention and acknowledged quite promising for bone tissue engineering. Herein, novel biomimetic bone scaffolds containing decellularized small intestinal submucosa matrix (SIS-ECM) and Sr 2+ /Fe 3+ co-doped hydroxyapatite (SrFeHA) are fabricated for the first time by the sophisticated self-assembled mineralization procedure, followed by cross-linking and lyophilization post-treatments. The results indicate the constructed SIS/SrFeHA scaffolds are characterized by highly porous structures, rough microsurface and improved mechanical strength, as well as efficient releasing of bioactive Sr 2+ /Fe 3+ and ECM components. These favorable physico-chemical properties endow SIS/SrFeHA scaffolds with an architectural/componential biomimetic bony environment which appears to be highly beneficial for inducing angiogenesis/osteogenesis both in vitro and in vivo . In particular, the cellular functionality and bioactivity of endotheliocytes/osteoblasts are significantly enhanced by SIS/SrFeHA scaffolds, and the cranial defects model further verifies the potent ability of SIS/SrFeHA to accelerate in vivo vascularization and bone regeneration following implantation. In this view these results highlight the considerable angiogenesis/osteogenesis potential of biomimetic porous SIS/SrFeHA scaffolds for inducing bone regeneration and thus may afford a new promising alternative for bone tissue engineering.